2021
DOI: 10.48550/arxiv.2112.10815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symplectic Model Reduction of Hamiltonian Systems on Nonlinear Manifolds

Abstract: Classical model reduction techniques project the governing equations onto linear subspaces of the high-dimensional state-space. For problems with slowly decaying Kolmogorov-nwidths such as certain transport-dominated problems, however, classical linear-subspace reducedorder models (ROMs) of low dimension might yield inaccurate results. Thus, the concept of classical linear-subspace ROMs has to be extended to more general concepts, like Model Order Reduction (MOR) on manifolds. Moreover, as we are dealing with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Remark 8.2. MOR for pHODEs is discussed for instance in Hesthaven (2017, 2019), Gugercin (2011), Borja, Scherpen andFujimoto (2023), Breiten and Unger (2022), Breiten, Morandin and Schulze (2022b), Buchfink, Glas and Haasdonk (2021), Chaturantabut, Beattie andGugercin (2016), Egger et al (2018), Fujimoto and Kajiura (2007), van der Schaft (2009, 2012), Ionescu and Astolfi (2013), Kawano and Scherpen (2018)…”
Section: Model-order Reductionmentioning
confidence: 99%
“…Remark 8.2. MOR for pHODEs is discussed for instance in Hesthaven (2017, 2019), Gugercin (2011), Borja, Scherpen andFujimoto (2023), Breiten and Unger (2022), Breiten, Morandin and Schulze (2022b), Buchfink, Glas and Haasdonk (2021), Chaturantabut, Beattie andGugercin (2016), Egger et al (2018), Fujimoto and Kajiura (2007), van der Schaft (2009, 2012), Ionescu and Astolfi (2013), Kawano and Scherpen (2018)…”
Section: Model-order Reductionmentioning
confidence: 99%
“…To this end, such methods rely on nonlinear and/or hybrid space-time approaches. For more details, we refer to [8,10,18,21,26,29,31].…”
Section: Introductionmentioning
confidence: 99%
“…While the field of symplectic model reduction of Hamiltonian systems has grown considerably in the recent years [35,1,15,33,6], progress on structure-preserving model reduction of Lagrangian systems has been less rapid. The intrusive model reduction for Lagrangian systems was introduced in [26] where the authors showed that performing a Galerkin projection on the Euler-Lagrange equations preserves the Lagrangian structure.…”
Section: Introductionmentioning
confidence: 99%